Quality of life results from the phase 3 REVEL randomized clinical trial of ramucirumab-plus-docetaxel versus placebo-plus-docetaxel in advanced/metastatic non-small cell lung cancer patients with progression after platinum-based chemotherapy - Pérol, Maurice; Ciuleanu, Tudor-Eliade; Arrieta, Oscar; Prabhash, Kumar; Syrigos, Konstantinos N.; Goksel, Tuncay; Park, Keunchil; Kowalyszyn, Ruben Dario; Pikiel, Joanna; Lewanski, Conrad R.; Thomas, Michael (Lung cancer, 2016)
Objectives - REVEL demonstrated that ramucirumab+docetaxel (RAM+DTX) improved overall survival, progression-free survival, and objective response rate in patients with advanced/metastatic non-small cell lung cancer with progression after platinum-based chemotherapy. This analysis examined quality of life (QoL) as assessed by the Lung Cancer Symptom Scale (LCSS) and clinician-reported functional status. - Materials and Methods - The LCSS includes 6 symptom and 3 global items measured on a 0-100-mm scale; higher scores represent greater symptom burden. LCSS and ECOG PS data were collected at baseline, every 3-week cycle, the summary visit, and at the 30-day follow-up. LCSS total score and Average Symptom Burden Index (ASBI) were calculated. The primary analysis compared time to deterioration (TtD) between treatment arms for all individual items and summary scores, defined as increase from baseline by ≥15mm using the Kaplan-Meier method and Cox regression. TtD to ECOG PS ≥2 was analyzed. - Results - There were 1253 patients randomized to receive RAM+DTX or placebo+docetaxel (PL+DTX). Across all assessments, LCSS compliance was approximately 75% and balanced across arms. The mean (SD) baseline LCSS total score was 27.3mm (17.08mm) on RAM+DTX and 29.6mm (17.59mm) on PL+DTX. At 30-day follow-up, mean (SD) LCSS total score was 32.0 (19.03) on RAM+DTX and 32.5 (19.87) on PL+DTX. The TtD for all LCSS scores was similar between treatment arms. Stratified HRs (95% CI) for LCSS total score and ASBI were HR=0.99 (0.81, 1.22), p=0.932 and HR=0.93 (0.75, 1.15), p=0.514 with approximately 70% of patients censored. TtD to PS≥2 was similar between treatment arms (HR=1.03 [95% CI: 0.85, 1.26], p=0.743) with approximately two-thirds of the patients censored. - Conclusion - In addition to improvement of clinical efficacy outcomes demonstrated in REVEL, these results suggest that adding ramucirumab to docetaxel did not impair patient QoL, symptoms, or functioning.